Statistical concepts a second course - Lomax, Richard G.; Hahs-Vaughn, Debbie L. (Routledge, 2012)
Consists of the last 8 chapters of Richard Lomax's best selling text, "An Introduction to Statistical Concepts, 2E". This work demonstrates how many statistical concepts relate to one another. It includes only the crucial equations. It covers a number of ANOVA and regression models: one-factor; multiple comparison; factorial; ANCOVA; and more